A review on incidences of foodborne diseases and interventions for a better national food safety system in Malaysia - Wahida Salleh,; Mohd Nizam Lani,; Wan Zawiah Wan Abdullah,; Tuan Zainazor Tuan Chilek,; Zaiton Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper reviews the trend and possible contributing factors that cause the incidence of foodborne illnesses as it is the major concern of food safety issues in Malaysia. Surveillance and monitoring done by the enforcement authorities have improved the food safety as the percentage of contravened samples and food premises closures have been decreased. Some factors that contribute to the emergence of the foodborne pathogens are cross contamination of foods and food handlers, eating behaviour and technology, globalisation, antimicrobial resistance bacteria and climate change. Main problems that contribute to the high rates of foodborne illnesses are poor practices of food handlers and lack of public awareness. Various interventions have been initiated by the Food Safety and Quality Division, Ministry of Health (MoH) to improve national food safety system through food handlers training programme, the establishment of Food Safety Information System of Malaysia (FOSIM) and Malaysia Foodborne Disease Network (MyFoodNet) as parts of strengthening the surveillance system and improving the effective enforcement of legislation and regulations. Continous collaboration between government and private sectors are crucial for a sustainable improvement for a better health of the nation.